Islamic Educational Institutions in Indonesia - Dwiyana Fitrianingrum (Asian Journal of Islamic Studies and Society, 2021)
This research is motivated by observational data which shows Islamic educational institutions in Indonesia.  To respond to this, researchers conducted action research aimed at improving learning outcomes.  The objectives to be achieved in this study include: (1) Knowing the types of Islamic educational institutions in Indonesia (2) Knowing the principles of Islamic education (3) Knowing the kinds of Islamic educational institutions in Indonesia.  The results showed that in Indonesia there are 3 kinds of educational institutions.